RETRACTED: Garden-Park Landscape Architecture and the formation of recreation areas (on the example of the cities of Uzbekistan) - Alieva Manzura; Daminova Umida; Ikromov Shavkat; Ikromova Mavluda; Zokirova Latofat (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001